REVIEW: MICROBIAL BIOCENOSES IN PRISTINE AQUIFERS AND AN ASSESSMENT OF INVESTIGATIVE METHODS - Goldscheider N.; Hunkeler D.; Rossi P. (My University, 2006)
The current knowledge of microbial biocenoses (communities) in pristine aquifers is presented in a review, which also discusses their relevance for questions of groundwater protection. Aquifers are heterogeneous on all scales and structured in a variety of habitats. The void spaces in many aquifers are small. The biocenoses are thus predominantly composed of microorganisms and, often, microinvertebrates. Larger voids and macroorganisms occur in karst cavities. Due to the absence of light, the biocenoses depend on chemical energy resources, which are, however, scarce in non-contaminated groundwater. The microorganisms thus show small cell sizes, low population densities and reduced activity; they developed specific strategies to survive oligotrophic conditions. The review also discusses the impact of contamination on the biocenoses, and the potential use of the biocenoses or specific organisms as indicators for groundwater quality, and the limits of this approach. Bacteria are either planktonic or attached to aquifer material, which requires both fluid and solid phase sampling. Most groundwater bacteria are viable but non-culturable. Consequently, cultivation techniques give an incomplete picture of the biocenoses, while methods from molecular microbiology provide genetic fingerprints of the entire community. Different analytical methods are available to count microorganisms, identify species, characterise microbial diversity, and measure activity. © Springer-Verlag 2005.
Keywords: ENVIRONMENTAL MICROBIOLOGY; GROUNDWATER PROTECTION; MICROECOLOGY; MICROBIAL COMMUNITY; NON-CONTAMINATED AQUIFER